INTEGRATION OF UPBRINGING AND MORAL VALUES - Ibodullayeva Zubayda Sherzodovna (The latest news and research in education, 2025)
The integration of upbringing and moral values stands as a fundamental pillar for fostering ethical behavior and social cohesion. This intersection is particularly salient in an increasingly diverse societal landscape, where complex cultural dynamics shape individual and collective values.